THU0249 Family history of autoimmune diseases as a risk factor for sjÖgren's syndrome: a case-control study. (1st June 2001) - Priori, R; Conti, F; Cassarà, E; Medda, E; Stazi, MA; Cesarotti, M; Rovere, P; Antonioli, C; Danieli, MG; Pietrogrande, M; Valesini, G
Abstract : Background: As far as we know, no epidemiological study is available regarding risk factors for Sjögren's syndrome (SS). Objectives: A multicentre case-control study was carried out in Italy to evaluate the relationship between SS and a history of autoimmune diseases (AD) in first degree relatives (FDR). Methods: Cases and controls were randomly selected and interviewed by trained medical doctors using a detailed questionnaire. The strenght of the association between family history of AD and SS was measured as an odds ratio (OR). The adjusted OR was obtained by unconditional logistic regression model and the potentially confounding covariates were family size, age and sex of proband. Results: A total of 143 eligible SS cases (EEC criteria, 1994) and 140 healthy controls were identified. 27/143 (18.8%) SS and 7/140 (5%) controls had one FDR with AD, 7/143 (4.9%) and 1/140 (0.7%) had two or more FDR with AD. Considering the proband with one FDR with AD (therefore belonging to a multiplex family) in comparison to probands without any FDR affected (belonging to a simplex family), the adjusted OR was 6.19 (95% CI 2.3–16.7); the risk is higher if the relatives are two or more: OR 19.2 (95% CI 1.69–216). Conclusion: This study indicates that a family history of autoimmune disorders is a risk factor for SS. Probands from multiplex families have an higher risk to have SS compared to simplex families. The risk increases with the number of FDR with AD.